Planejamento de fármacos, biotecnologia e química medicinal: Aplicações em doenças infecciosas - Guido, Rafael V.C. [UNESP]; Andricopulo, Adriano D.; Oliva, Glaucius (FapUNIFESP (SciELO), 2010)
Current drug design strategies are based on the understanding of the physiopathology of diseases, biochemical pathways and selection of molecular targets. Modern biotechnological tools have provided valuable information to facilitate the discovery of new drug candidates. Medicinal chemistry has a vital role in a variety of processes aimed at the identification of bioactive substances and the development of lead-compounds with optimized pharmacodynamic and pharmacokinetic properties. The present paper presents some fundamental aspects of biotechnology and medicinal chemistry as useful tools in the design of new chemical entities for the therapy of infectious diseases.
Keywords: Drug design; Enzymes; Infectious diseases; Inhibitors; Medicinal chemistry; Molecular modeling